Espionage - Bachrach, Deborah, 1943- (San Diego, CA : Lucent Books, 1992)
Traces the history of spying and the issues it raises for present and future generations.
Includes bibliographical references (p. 106-108) and index.
Keywords: Espionage -- History -- Juvenile literature; Espionage -- History